The un-Trollopian Trollope: some notes on the Barsetshire novels - Pérez Pérez, Miguel Ángel (Revista Alicantina de Estudios Ingleses, 1999)
The six Barsetshire novels are not only Anthony Trollope's most popular ones, but also those which are usually considered to represent the author at his mildest and most conventional, as regards the Victorian social and ethical codes. Without entirely disregarding this view, this paper argues that Trollope disguises many of his own opinions behind an apparently unproblematic presentation of characters, situations and attitudes. The essay is therefore an attempt to delineate some of these techniques of "concealment", with the aim of exposing some of the double readings discoverable in Trollope's novels.